2018
DOI: 10.1111/ggi.13467
|View full text |Cite|
|
Sign up to set email alerts
|

Nutritional intake is associated with activities of daily living and complications in older inpatients with stroke

Abstract: Energy intake during the first week after admission affected improvement of ADL and onset of complications during hospitalization in geriatric stroke inpatients. Geriatr Gerontol Int 2018; 18: 1334-1339.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 29 publications
1
19
0
1
Order By: Relevance
“…Recently, combined intervention has been viewed with keen interest; the effects of combined intervention on improving muscle strength or mass has gained a certain consensus [ 1 , 2 , 3 , 4 , 5 , 6 , 17 , 18 ], and the range of its use is expanding. Previous studies were done in patients with stroke [ 10 ], hip fracture [ 19 ], and artificial joint replacement [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, combined intervention has been viewed with keen interest; the effects of combined intervention on improving muscle strength or mass has gained a certain consensus [ 1 , 2 , 3 , 4 , 5 , 6 , 17 , 18 ], and the range of its use is expanding. Previous studies were done in patients with stroke [ 10 ], hip fracture [ 19 ], and artificial joint replacement [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis was conducted by a co-investigator (AK) who was independent of the recruitment, intervention, and data collection. Based on a study by Yoshimura [ 10 ], the minimal sample size was calculated using two-way repeated measures analysis of variance to examine significant differences between the groups (α = 0.05, power = 0.8, effect size = 0.5); 23 participants per group were required. The two groups were created by random assignment of the time of supplementation, including a breakfast group ( n = 23) and post-exercise group ( n = 23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, one of the studies was excluded because it had been retracted by the editors because of concerns about data integrity and scientific misconduct [22,23]. From the nine remaining studies, see Table 1, four were multicenter studies [24,25,26,27]. Two interventions were commenced in the acute stroke phase [25,28] while others were including chronic stroke patients either during rehabilitation as inpatients [29,30] or outpatients [24].…”
Section: Resultsmentioning
confidence: 99%
“…13 In a retrospective study, Kokura et al reported that energy intake affected the improvements in the ADL of older stroke patients. 14 These reports implied the importance of intensive nutritional support for acute stroke patients with malnutrition risk. In contrast, Pellicane et al reported that improvement in the ADL was not associated with energy intake.…”
Section: Introductionmentioning
confidence: 99%